2023
DOI: 10.3389/fimmu.2023.1209947
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated macrophages mediate resistance of EGFR-TKIs in non-small cell lung cancer: mechanisms and prospects

Abstract: Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) are the first-line standard treatment for advanced non-small cell lung cancer (NSCLC) with EGFR mutation. However, resistance to EGFR-TKIs is inevitable. Currently, most studies on the mechanism of EGFR-TKIs resistance mainly focus on the spontaneous resistance phenotype of NSCLC cells. Studies have shown that the tumor microenvironment (TME) also mediates EGFR-TKIs resistance in NSCLC. Tumor-associated macrophages (TAMs), one of the centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 140 publications
0
3
0
Order By: Relevance
“…It was demonstrated that treatment with osimertinib could promote the formation and release of wild type EGFR (wtEGFR)-harbouring exosomes in wtEGFR-expressing NSCLC cells by upregulating a Rab GTPase (RAB17), and exosome-mediated intercellular transfer of wtEGFR further triggered osimertinib resistance in mutEGFR NSCLC through activating downstream PI3K/AKT and MAPK signaling pathways [ 383 ]. In addition, exosomes derived from M2 type TAMs were also showed to confer osimertinib resistance in NSCLC through MSTRG.292666.16‑​miR‑6836‑​5p‑MAPK8IP3 axis, suggesting that targeting TAMs may help to circumvent resistance of EGFR-TKIs [ 384 , 385 ]. The monoclonal antibody trastuzumab is the first HER2-targeted drug approved for the treatment of patients with HER2-positive breast cancer [ 386 ].…”
Section: Tumor Biology Of Exosomesmentioning
confidence: 99%
“…It was demonstrated that treatment with osimertinib could promote the formation and release of wild type EGFR (wtEGFR)-harbouring exosomes in wtEGFR-expressing NSCLC cells by upregulating a Rab GTPase (RAB17), and exosome-mediated intercellular transfer of wtEGFR further triggered osimertinib resistance in mutEGFR NSCLC through activating downstream PI3K/AKT and MAPK signaling pathways [ 383 ]. In addition, exosomes derived from M2 type TAMs were also showed to confer osimertinib resistance in NSCLC through MSTRG.292666.16‑​miR‑6836‑​5p‑MAPK8IP3 axis, suggesting that targeting TAMs may help to circumvent resistance of EGFR-TKIs [ 384 , 385 ]. The monoclonal antibody trastuzumab is the first HER2-targeted drug approved for the treatment of patients with HER2-positive breast cancer [ 386 ].…”
Section: Tumor Biology Of Exosomesmentioning
confidence: 99%
“…Data supporting anti-CD47 as an active therapy combined with the potential of small-molecule therapies to modify macrophage polarity supported development of a platform that would identify combination therapies that could increase (or decrease) the activity of anti-CD47 in NSCLC. This strategy could have clinical relevance, as TAMs, likely M2 like, have been shown to drive resistance to EGFR inhibitors in NSCLC ( 14 ). Vaccaro and colleagues implemented an innovative drug screening platform to find therapies that have the ability to increase cancer cell susceptibility to macrophage-induced destruction ( 15 ).…”
Section: Exploiting Phenotypic Plasticity Of Macrophagesmentioning
confidence: 99%
“…Among these, tumor-associated macrophages (TAMs) are the most abundant (15,16). Macrophages in the normal body have valued biological functions, including processing and presenting antigens, regulating immunity, resisting microorganisms, clearing foreign bodies, phagocytosis, and tissue remodeling (17)(18)(19)(20). In specific microenvironments, macrophages polarize into subtypes with various biological capabilities, i.e., M1-type macrophages and M2-type macrophages (21-23).…”
Section: Introductionmentioning
confidence: 99%